¿La clave está en Confucio? - Bernarte Aguirre, Berta (Huarte de San Juan. Geografía e Historia, 2006)
China is living a wave of economic reforms and social changes. In the middle of this intellectual turmoil, some scholars look back to the past and turn their eyes to Confucius, searching for a new approach to Chinese tradition. They try to find if the Chinese heritage is able to provide some clues to modernize China. Therefore, many have seen traditional Chinese culture as being a hindrance to modernization and the main cause of the geostrategic humiliations in the XIX century. Could Confucius be a way of democratization?